2022
DOI: 10.3390/horticulturae8111021
|View full text |Cite
|
Sign up to set email alerts
|

Using Sigmoid Growth Models to Simulate Greenhouse Tomato Growth and Development

Abstract: Mathematical modeling has been used to describe the characteristics of crop growth. Establishing a growth model can help to better understand the responses of crops to their environment and improve the efficiency of agricultural production. This study establishes empirical growth models to predict the growth of greenhouse tomato. In this study, we collected beef tomato (Solanum lycopersicum cv. ‘993′) growth data over two crop seasons in Taiwan and established growth models by employing the commonly used Gompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The overall growth process of crops shows a trend of "gradual growth-rapid growthslow growth", forming an "S"-shaped curve [30], which is supported by the logistic model [19]. Therefore, this model was used to quantitatively analyze the dynamic development of plant height and stem diameter of protected tomatoes under different irrigation water salinities.…”
Section: Dynamic Simulation Of Plant Height and Stem Diameter Of Toma...mentioning
confidence: 93%
See 1 more Smart Citation
“…The overall growth process of crops shows a trend of "gradual growth-rapid growthslow growth", forming an "S"-shaped curve [30], which is supported by the logistic model [19]. Therefore, this model was used to quantitatively analyze the dynamic development of plant height and stem diameter of protected tomatoes under different irrigation water salinities.…”
Section: Dynamic Simulation Of Plant Height and Stem Diameter Of Toma...mentioning
confidence: 93%
“…Furthermore, the fully correlated model provided a good fit for the growth patterns of all four crops. Fang et al [19] used the commonly used Gompertz and logistic curves to establish growth models, taking the days after transplanting and cumulative growing degree days as independent variables to simulate the correlation between these variables and five growth indices. The results indicated that the logistic model estimated critical points were closer to the expected values than the Gompertz model and were more suitable for tomato crops in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…For establishing the growth model, GDD (Equation ( 17)) [27] was used as the input variable; LAI, fresh fruit weight, and aboveground dry matter were utilized as the output variables. Two sigmoid models, namely the Logistic (Equation ( 18)) [35] and Gompertz (Equation ( 19)) [36], were used to fit the growth data and both require three parameters to characterize tomato growth:…”
Section: Sigmoid Model For Predicting Greenhouse Tomato Growthmentioning
confidence: 99%
“…The main advantages of the Logistic and Gompertz models lie in their simplicity and interpretability. These models frequently describe plant height, biomass accumulation, and leaf area index (LAI) as a function of time or GDD [27][28][29]. The simulation of crop growth can provide useful information for adjusting management practices and schedules [27,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation